Imagining Zoos - Rothfels, Nigel (Captures)

(untitled) (Figura, Centre de recherche sur le texte et l'imaginaire, 2022)
Beginning with paintings of dodos and cassowaries by the Flemish artist Roelandt Savery, this essay traces continuities between early-modern European menageries and 21st-century zoos. Arguing that modern zoos persist in attempting to present an imaginary world of superabundance, the article shows how today’s zoo simulations, mid-20th-century zoo-themed board games and toys, and a mid-19th-century paper zoo echo older attitudes toward “nature,” the “natural,” and the “exotic.”